Unaffected mosaic C9orf72 case: RNA foci, dipeptide proteins, but upregulated C9orf72 expression - McGoldrick, Philip (Neurology, 2018)
OBJECTIVE: Suggested C9orf72 disease mechanisms for amyotrophic lateral sclerosis (ALS) and frontotemporal lobar degeneration include C9orf72 haploinsufficiency, G(4)C(2)/C(4)G(2) RNA foci, and dipeptide repeat (DPR) proteins translated from the G(4)C(2) expansion; however, the role of small expansions (e.g., 30–90 repeats) is unknown and was investigated here. METHODS: We conducted a molecular and pathology study of a family in which the father (unaffected at age 90) carried a 70-repeat allele in blood DNA that expanded to ≈1,750 repeats in his children, causing ALS. RESULTS: Southern blotting revealed different degrees of mosaicism of small and large expansions in the father's tissues from the CNS. Surprisingly, in each mosaic tissue, C9orf72 mRNA levels were significantly increased compared to an ALS-affected daughter with a large expansion. Increased expression correlated with higher levels of the 70-repeat allele (the upregulation was also evident at the protein level). Remarkably, RNA foci and DPR burdens were similar or even significantly increased (in cerebellum) in the unaffected father compared to the daughter with ALS. However, the father did not display TDP-43 pathology and signs of neurodegeneration. CONCLUSION: The presence of RNA foci and DPR pathology was insufficient for disease manifestation and TDP-43 pathology in the mosaic C9orf72 carrier with upregulated C9orf72 expression. It is important to conduct an investigation of similar cases, which could be found among unaffected parents of sporadic C9orf72 patients (e.g., 21% among Finnish patients with ALS). Caution should be taken when consulting carriers of small expansions because disease manifestation could be dependent on the extent of the somatic instability in disease-relevant tissues.